Characterization of the lectin from females of Phlebotomus duboscqi sand flies - Volf, Petr; Skarupová, Sona; Man, Petr (European journal of biochemistry, 2002)
Lectin from females of the important sand fly vector, Phlebotomus duboscqi (Diptera: Psychodidae), was isolated by immunoaffinity chromatography using a minicolumn with immobilized anti-lectin immunoglobulins. Carbohydrate-binding specificity of active fractions corresponded to that of midgut and salivary gland lysates. Haemagglutination was inhibited by d-glucosamine, d-galactosamine and d-mannosamine. The homogeneity and molecular mass of the purified lectin was examined by SDS/PAGE in both reducing and nonreducing conditions. The active fractions showed one band strongly stained by Coomassie blue or silver nitrate; the molecular mass of the lectin was 42 kDa under nonreducing and 44 kDa under reducing conditions. SDS/PAGE of active fractions from the gel filtration revealed four to six protein bands, but the 42/44-kDa protein present in all active fractions was the only component reacting with specific antibodies in Western blots. Localization of the lectin in the gut of females was studied using indirect immunofluorescence on sections. The positive reaction of specific antibodies was localized in the lumen and along the microvillar surfaces of epithelial cells. The lectin was partially sequenced and characterized by MS. Peptide maps were obtained by MALDI-TOF MS, and several sequence tags were identified from tandem mass spectra on an ion trap. These sequences displayed high similarity to salivary protein precursors previously identified in a cDNA library of the sand flies Phlebotomus papatasi and Lutzomyia longipalpis. Two main hypotheses on the role of female lectin in Leishmania development are discussed.
Keywords: lektiny; Gene Library; genová knihovna; Protein Structure, Tertiary; fluorescenční mikroskopie; terciární struktura proteinů; western blotting; vysokoúčinná kapalinová chromatografie; komplementární DNA; Digestive System; Hemagglutinins; Chromatography, Gel; elektroforéza v polyakrylamidovém gelu; imunoglobuliny; králíci; Chromatography, High Pressure Liquid; chromatografie afinitní; Blotting, Western; Animals; Electrophoresis, Polyacrylamide Gel; Microscopy, Fluorescence; ženské pohlaví; Lectins; hemaglutininy; zvířata; gelová chromatografie; Rabbits; erytrocyty; Erythrocytes; spektrometrie hmotnostní - ionizace laserem za účasti matrice; DNA, Complementary; Female; Immunoglobulins; Chromatography, Affinity; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Phlebotomus; trávicí systém